ANALISIS KESELAMATAN PEJALAN KAKI PADA SIMPANG BERSINYAL - Tas'an Junaedi (UNIVERSITAS LAMPUNG, 2014)
Pedestrians crossing road at the signalized intersection has a high risk as victims of traffic acci- dents, it is because the time of pedestrian to cross the road not taken into account by the cycle time of traffic lights. The purpose of this study was to evaluate the intersection and associate it with the behavior of pedestrians crossing the road. The results showed that the walking speed of pedestrians can not crossing on red all period and setting time at traffic lights at the intersection has not accommodate a pedestrian to crossing. to improve the safety and comfort of pedestrians, then at the intersection countdown signal must be installed equipment, the equipment is minimal in-set time of 15 seconds to allow time for pedestri- ans to crossing.